Preparation of enantiopure butane-2,3-diacetals of glycolic acid and alkylation reactions leading to alpha-hydroxyacid and amide derivatives. - Ley, S; Diez, E; Dixon, D; Guy, RT; Michel, P; Nattrass, G; Sheppard, T (2004)
The preparation of butane-2,3-diacetal protected glycolic acid and related systems is described together with highly selective alkylation reactions of (R,R) and (S,S) butanediacetal protected glycolic acid. These compounds are readily deprotected to give enantiopure alpha-hydroxyacids, alpha-hydroxyesters or alpha-hydroxyamides by suitable choice of conditions.